2010
DOI: 10.1002/app.33167
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive shape memory characteristics of polyurethane electrospun web

Abstract: Electrospun web (ESW) was manufactured and its performance was evaluated to investigate its applicability as an intelligent clothing material using shape memory polymers. Mixtures of various compositions were applied to make the shape memory polyurethane (SMPU) films and the polyurethane with the best shape memory performance was then selected to make the ESWs. The structural and thermal properties, as well as the shape memory behavior were evaluated. The air permeability, the water vapor transmission, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 28 publications
1
39
0
Order By: Relevance
“…Cell sizes from these 2D images may be estimated using the algorithm in ASTM D3576 by counting the number of intersections of pore walls with a reference line. Planar 2D images of porous surfaces are also often reported using SEM, such as the SEM images of the porous SMPs fabricated by electrospinning and salt leaching, reported by Chung, et al [27, 61] , as shown in Figure 5. While 2D images are informative, three dimensional structures allow for a more comprehensive structural characterization.…”
Section: Characterization Of Porous Smp Substratesmentioning
confidence: 95%
See 2 more Smart Citations
“…Cell sizes from these 2D images may be estimated using the algorithm in ASTM D3576 by counting the number of intersections of pore walls with a reference line. Planar 2D images of porous surfaces are also often reported using SEM, such as the SEM images of the porous SMPs fabricated by electrospinning and salt leaching, reported by Chung, et al [27, 61] , as shown in Figure 5. While 2D images are informative, three dimensional structures allow for a more comprehensive structural characterization.…”
Section: Characterization Of Porous Smp Substratesmentioning
confidence: 95%
“…[35, 58-60] Chung and Park fabricated polyurethane SMP foams from a segmented thermoplastic polyurethane using salt leaching, [27] and Chung, Kang, and co-workers also fabricated an electrospun web using the same thermoplastic polyurethane. [61] Domeier [62] and Lee [19] also studied polyurethane based SMP foams (Table 1). …”
Section: Chemical Classes Of Porous Smpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Porous epoxies, polyurethanes and similar materials have been proposed for use in separations, 115 encapsulation and electrical insulation of components in microelectronics, [116][117][118] battery separators 119 and stimuli-responsive textiles. 120 As a first example of the utility of BmE-derived, nanoporous PE as a nanocasting template, we have generated nanoporous epoxy and polyurethane monoliths. 6 In the former case, glycidyl end-capped poly(bisphenol A-co-epichlorohydrin) (Aldrich, M n B348 g mol À1 ) and 4,4¢-methylenedianiline (Aldrich) were used as monomers, mixed in a stoichiometric molar ratio of 2:1 poly(bisphenol A-coepichlorohydrin):4,4¢-methylenedianiline (see Scheme 2).…”
Section: Nanoporous Thermosetting Polymersmentioning
confidence: 99%
“…A number of multiple functional materials have been electrospun into nanofibers used in different application fields. SMPs in the form of fibers are generating great interest in structural and functional applications because they have well-developed surface area, porous structure, and are easy adsorption, filtration, and penetration, as well as deformation (Cha et al, 2005;Ji et al, 2006;Kotek, 2008;Zhuo et al, 2008a;Chung et al, 2011).…”
Section: Introductionmentioning
confidence: 99%